More Than Politics: How Personality Trait and Media Technology Use Affect Vote Likelihood During the 2020 U.S. Presidential Election. (March 2022) - Zhong, Bu; Sun, Tao; Forde, Sydney; Payne, Gregory
Considerable work has been devoted to studying voter behavior in U.S. presidential elections by analyzing their political participation and attitude toward political advertising. Less is known about how other factors may alter voter behavior like personality traits and use of information and communication technology (ICT). This study analyzes vote likelihood among American young voters and their parents ( N = 674) after they watched four presidential campaign commercials . It proposes a hierarchical mediation model highlighting the need for cognition (NFC) impact on vote likelihood through the mediation of power use of ICT applications, political participation and trust in negative advertising. This study has revealed both the direct effect of NFC on vote likelihood, and the indirect relationship between NFC and vote likelihood that is mediated by power use of ICT applications. The findings should enrich the literature of vote likelihood by highlighting the effects of need for cognition and ICT usage.